Families and New Media Comparative Perspectives on Digital Transformations in Law and Society - Dethloff, Nina; Kaesling, Katharina; Specht-Riemenschneider, Louisa (Juridicum - Schriften zum Medien-, Informations- und Datenrecht, 2023)
The open access edited volume addresses children's rights and their ability to act in the digital world. The focus is on the position of children as subjects with their own rights and developing capacities. Their consideration by parents, courts and legislators is critically examined. Aspects of digital parenting, especially educational practices and strategies in the context of social media, are analyzed with regard to the tension between protection and participation of children. The edited volume brings debates on privacy and data protection together with those from tort, family and intellectual property law, while also examining the role of families and children in the regulation of data and digital economies, especially online platforms. Legal reflections from Germany, Israel, Portugal and the United States of America are complemented by perspectives from media studies, political science, educational science and sociology of law.